Growth strategies and value creation: what works best for stock exchanges? - Iftekhar Hasan; Heiko Schmiedel; Liang Song (European Central Bank (ECB), 2010)
In recent years, demutualized stock exchanges have been increasingly engaging in M&A and alliance activities. To examine the effect of these growth strategies on exchange shareholders' value creation, we focus on 14 public stock exchanges and investigate their short-run share price responses to the formation of 110 M&As and alliances all over the world spanning the period 2000-2008. Our findings show that the average stock price responses for M&As and alliances are positive. M&As create more value than alliances. For alliances, joint ventures generate more value than non-equity alliances. More value accrues when the integration is horizontal (cross-border) than when it is vertical (domestic). Additionally, there is evidence of learning-by-doing effects in stock exchange integration activities. Finally, we find that the better the shareholder protection, accounting standards and capital market development in the partner exchange's country, the higher the merger and alliance premium for our sample exchange. These patterns are consistent when we examine the exchanges' long-run performance.
Keywords: L22; G32; D23; 330; exchanges; joint ventures; mergers and acquisitions; network organization; strategic alliances; Börse; Übernahme; Strategische Allianz; Joint Venture; Börsenkurs; Welt